Demographic Factors, Stage of Disease and Adherence of Antiretroviral Drug Therapy in HIV/AIDS - เรือนสว่าง, พรศิริ; จงถาวรสถิตย์, สุกัญญา; ประสิทธิศิริกุล, วิศิษฏ์; ลิ้มเจริญ, กรุณา; ลิ้มเจริญ, กรุณา; เมืองไพศาล, เกศกนก; สิริวโรทัย, เยาวลักษณ์ (Disease Control Journal, 2011)
This study was retrospective study. 3,622 Samples of HIV/AIDS patients were 18 years old and over and first visit at 3 hospitals in Thailand, 2007. Data were collected from patient histories in the special database program. This study examines the relationship between demographic factors, stage of disease and adherence among patients receiving HAART. Adherence was used self-report questions and add together to get total score equal 16. Data analysis was used Multiple Logistic Regression. Multivariate analysis found that only hospital, age at HIV infected, gender, marital status, education, and stage of disease are statistically significant. The odds of adherence patients adhering to the HAART of the patient fromat San Pa Tong hospital and Lop Buri hospital were greater 33.9 and 6.3 times greater compared to patients at Bamrasnaradura Infectious Diseases Institute, respectively. The odds of adherence patients aged 25-34, 35-44, and 45 years old and over adhering to antiretroviral drug were greater compared to patients aged 18-24 years old. The odds of adherence female patients' adherence were greater 1.19 times compared to male patients. The odds of adherence for the married patients were greater 1.2 times compared to single patients. The odds of adherence no education patients with no education were greater compared to higher education patients. Patients with symptomatic and AIDS are less likely to have adherence than compare to asymptomatic patients. The outcome of this study suggested that adherence among patients receiving HAART should concern about was related to demographic factors and stage symptomatic of disease. We should emphasize on knowledge, attitude, practice, mental support and continuous treatment among symptomatic and AIDS patients.